The physiological condition of orphaned African elephants (Loxodonta africana) - Parker, Jenna Marie, author; Wittemyer, George, advisor; Crooks, Kevin, committee member; Hobbs, Tom, committee member; Pejchar, Liba, committee member (Colorado State University. Libraries, 2021)
To view the abstract, please see the full text of the document.